2017
DOI: 10.1007/jhep05(2017)015
|View full text |Cite
|
Sign up to set email alerts
|

Resonant slepton production and right sneutrino dark matter in left-right supersymmetry

Abstract: Right-handed sneutrinos are natural components of left-right symmetric supersymmetric models where the gauge sector is extended to include right-handed weak interactions. Unlike in other models where right-handed sneutrinos are gauge singlets, here the right sneutrino is part of a doublet and could be a dark matter candidate whose annihilation proceeds via gauge interactions. We investigate this possibility, and find that relic density, low-energy observable and direct supersymmetry search constraints can be s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 142 publications
1
33
0
Order By: Relevance
“…Because of the left-right symmetry, the righthanded fermions exist in SU(2) R doublets, making the right-handed neutrino a necessary ingredient in the model. In addition these models have several possible dark matter candidates, see [5], and may possibly solve both the strong and weak CP-problems.…”
Section: Gauge Extension Susylrmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the left-right symmetry, the righthanded fermions exist in SU(2) R doublets, making the right-handed neutrino a necessary ingredient in the model. In addition these models have several possible dark matter candidates, see [5], and may possibly solve both the strong and weak CP-problems.…”
Section: Gauge Extension Susylrmentioning
confidence: 99%
“…Recently it was found that the gauge and Higgs sectors can also significantly contribute to the doubly charged Higgs mass, which opens up a window for lighter right sleptons and sneutrinos [22]. To obtain a heavy enough doubly charged Higgs boson, we set the λ R parameter to a large value, which leads to a large contribution to the doubly charged Higgs boson mass from the Higgs sector [5].…”
Section: Gauge Extension Susylrmentioning
confidence: 99%
See 3 more Smart Citations